Becoming a Gordon Craig: Micheál mac Liammóir and Edward Gordon Craig’s Shared Beliefs and Performances of Self - Chris Moran (Review of Irish Studies in Europe)
Micheál mac Liammóir (1898-1978) and Edward Gordon Craig (1872-1966) shared many similarities: both were actors, designers, directors, and writers, and both rejected the realist tradition dominant in the theatre of their times. Craig’s developments in design throughout Europe laid a path for mac Liammóir to follow; indeed, mac Liammóir begins his autobiography All for Hecuba (1946) with the claim, ‘I would become [...] a Gordon Craig’. However, their affinities were not only in design and other aspects of theatre practice but in their shared artistic beliefs and performances of identity. This article will examine what mac Liammóir might have meant by ‘becoming a Gordon Craig’, first by considering Craig’s reputation and comparing both artists’ biographies. By contextualising Craig’s collaboration with W. B. Yeats at the Abbey Theatre, and Yeats’ influence on mac Liammóir, the article seeks to define the shared beliefs of mac Liammóir and Craig. Finally, by placing mac Liammóir’s reinvention and performance of self within a wider modernist context, an argument will be made for considering mac Liammóir in light of Craig’s concept of ‘The Über-Marionette’.